Pseudoceroximes A–E and Pseudocerolides A–E – Bromotyrosine Derivatives from a Pseudoceratina sp. Marine Sponge Collected in the South China Sea. Issue 17 (27th April 2020) - Chen, Mengxuan; Yan, Yizhen; Ge, Hengju; Jiao, Wei‐Hua; Zhang, Zhizhen; Lin, Hou‐Wen
Abstract : 15 new bromotyrosine‐derived compounds, pseudoceroximes A–E (1 –5 ), pseudocerolides A–E (6 –10 ), 13‐ketohemifistularin 3 (11 ), and ceratinines J–M (12 –15 ), were isolated from a Pseudoceratina sp. marine sponge collected in the South China Sea. The planar structures of all compounds were established based on extensive NMR spectroscopic analyses and HRESIMS data. Their absolute configurations were assigned by a combination of modified Mosher's method, ECD calculations and a single‐crystal X‐ray diffraction experiment. Pseudoceroximes A–D (1 –4 ) represent the first examples of the oxime‐type bromotyrosine derivatives possessing the 2‐oxazolidone ring. Pseudoceroximes A (1 ) and B (2 ) and pseudocerolide C (8 ) showed antibacterial activity against methicillin‐resistant Staphylococcus aureus ATCC 43300 with MIC values of 5.2–7.1 µm . Additionally, pseudoceroximes B (2 ) and D (4 ) exhibited moderate antiproliferative activity against two human glioma cell lines U87MG and U251. Abstract : 15 new bromotyrosine‐derived compounds were isolated from a Pseudoceratina sp. marine sponge collected in the South China Sea. Their structures were assigned by Mosher's method, ECD calculations and X‐ray analysis. Pseudoceroximes A (1 ) and B (2 ) and pseudocerolide C (8 ) showed antibacterial activity against methicillin‐resistant Staphylococcus aureus ATCC 43300 with MIC values of 5.2–7.1 µm .